LA DIVERSIDAD CULTURAL Y SU IMPACTO EN EL APRENDIZAJE DE LOS ESTUDIANTES DEL 5TO. AÑO DE EGB, DE LA UNIDAD EDUCATIVA DEL MILENIO SIMÓN BOLÍVAR - GARCES CERCADO NAYELLY NICOLE (2024)
The case study explored the challenges and opportunities associated with promoting cultural inclusion in educational settings, important challenges are identified, such as the lack of educational material focused on ethnic and cultural diversity and the need to master inclusive pedagogical strategies, however . , the opportunities to enrich the educational environment with many cultural perspectives and traditions were emphasized, which promotes more complete and meaningful learning, the present research work called cultural diversity and its impact on the learning of 5th year EGB students . , from the Unidad Educativa Del Milenio Simón Bolívar, aims to synthesize the influence of cultural diversity in the learning process of students in the 5th year of Basic General Education at the Unidad Educativa del Milenio Simón Bolívar. Being a case study, its development is based on a qualitative methodology, and through the bibliographic research technique, it was possible to find through a very thorough search all the information necessary to develop the two variables of the research topic, as a research instrument. . The interview was used to obtain information about certain questions that arise in relation to the topic that consists of 4 questions directed to the objectives. A close relationship began between the distinctive characteristics of each culture present in the school environment and the learning process. The importance of understanding and valuing cultural differences is recognized to promote an inclusive and equitable educational environment.